Clinical and Socioeconomic Predictors of Outcomes in Severe Traumatic Brain Injury - Shakir, Mohammad; Kumar, Pankaj; Pandey, Tripurari; Singh, Manish (Journal of Neonatal Surgery, 2025)
Background: Traumatic brain injury (TBI) is a major cause of morbidity and mortality, particularly among young people in developing countries. Limited healthcare resources complicate the management of severe TBI, making accurate prognosis prediction essential. Factors such as socioeconomic status, access to emergency care, and alcohol use significantly influence outcomes. This study aims to identify clinical and socioeconomic factors predicting patient outcomes in severe TBI cases. Methodology: This prospective observational study was conducted over two years at King George’s Medical University in Lucknow, India, involving 820 patients with isolated severe TBI. Patients were assessed at admission and again at three months using the Glasgow Outcome Scale Extended (GOSE) to determine outcomes. Statistical analysis was performed using SPSS version 21, with a significance level set at p < 0.05. Results: Among the 820 TBI patients, 66.9% were male, with a mean age of 35.68; SD:17.36 years. Road traffic accidents were the leading cause of injury (82.9%), and 65.4% of patients did not survive. Key complications included seizures (10.7%) observed. The Glasgow Coma Scale (GCS) score at admission and various imaging scores (Marshall and Rotterdam) were significantly associated with outcomes, with a GCS of 5-6 indicating poor prognosis (p < 0.0001). Logistic regression analysis demonstrated strong predictive value for survival, achieving 77.46% sensitivity and 92.91% specificity, with an AUC of 0.9227. Conclusion: Severe TBI mainly affects those aged 20-30, with worse outcomes for patients over 50. Poor prognosis is linked to low GCS scores, seizures, alcohol use, and abnormal pupil responses, highlighting the need for improved predictive models.